A CASE STUDY ON THE INFLUENCE OF SOCIO - ECONOMIC STATUS OF WOMEN ON INFANT HEALTHCARE IN KERALA STATE - Reshma.C.U; Sheheersha.S.K and V. Saravanabavan
Kerala offers an interesting paradox of social advancement and economic stagnation. Women in the state inspite of enjoying better status and position compared to other parts of the country have low levels of participation in economic activity. The empowerment of women is anchored to their economic status in the society .This study is an attempt to understand the association between women’s work and children’s well being in a specific social setting. Increase in work participation of women outside the house tends to reduce the desired number of children as the opportunity cost of child bearing and rearing is high. Also, women who work outside home get better exposed to available options of contraception. There are two mutually compensating effects of women’s participating on child survival and care. The first one is the positive effect accruing from mother’s income. The mother’s work participation enhances the family income, which in turn has a positive impact on child nutrition and health. The second is the negative impacts on children well being. The labour force participation of the mother can have an adverse impact on child health as the child may not get full attention from his mother and may even have to forego the benefits of breastfeeding. Objectives of the study are to understand women’s work and its specifications, to examine the differentials in child health status in relation to the work characteristics of women, to analyze the causal mechanisms in the association between women’s work and child healthcare etc. Conceptual and analytical approaches used for the present study. This study employs multiple data sets that include both quantitative and qualitative information. Arc.GIS 9.3 used for mapping and SPSS used for statistical analysis